Genetic variation within and among species of five sections of the genus Arachis L. (Leguminosae) using RAPDs - Dos Santos, V. Sérgio Emílio [UNESP]; Gimenes, M. Aparecido [UNESP]; Montenegro Valls, J. Francisco; Lopes, C Romero [UNESP] (Springer Nature, 2003)
Some Arachis species are widely used as commercial plants, e.g. the groundnut A. hypogaea, an important source of good quality protein and oil, and A. pintoi and A. glabrata, that are utilized as forage species. Germplasm of most Arachis species is available in germplasm banks. However, little it is known about the genetic attributes of this germplasm, and mainly about its genetic variability, which is very important for its maintenance. In the present study RAPDs were used to assay the genetic variation within and among 48 accessions of five sections of the genus Arachis and to establish the genetic relationships among these accessions. Ten of 34 primers tested were selected for DNA amplification reactions since they yielded the largest numbers of polymorphic loci. A dendrogram was constructed based on data from the 10 primers selected. Eighty RAPD polymorphic bands were analyzed among the accessions studied. The relationships among species based on RAPDs were similar to those previously reported based on morphological, cytological and crossability data; demonstrating that RAPDs can be used to determine the genetic relationships among species of the different sections of the genus Arachis. In general, wide variation was found among accessions and low variation was found within the accessions that had two or more plants analyzed. However, higher polymorphism was found in the section Trierectoides and in one accession of A. major, indicating that generalizations should be avoided and each species should be analyzed in order to establish collection and maintenance strategies.
Keywords: Arachis; Genetic variation; Germplasm; Groundnut; Molecular markers; RAPD; genetic variation; Arachis glabrata; Arachis hypogaea; Arachis major; Arachis pintoi; Embryophyta; Fabaceae